(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Poverty is predominantly a ruralphenomenon. Agricultural wage earners, small and marginal farmers and casualworkers engaged in non- agricultural activities, constitute the bulk of ruralpoor. Small land holdings and their un- remunerative productivity are the causeof poverty among agrarian populace. Poor educational and health standards; andlack of other vocational skills also perpetuate poverty. Due to the poorphysical, social and financial capital base, a large proportion of the peopleare forced to seek employment in vocations with extremely low levels ofproductivity and wages. The creation of employment opportunities for the unskilledworkforce has been a major challenge for development planners andadministrators. Substantial number of landless and small farmers is dependenton wage employment and experience employment seasonally. The worst affected arethe women and children. To provide employment and eradicate poverty, thegovernment introduced several schemes and one among those schemes is SGSY.